Risk Stratification of Patients With Current Generation Continuous-Flow Left Ventricular Assist Devices Being Bridged to Heart Transplantation. Issue 2 (March 2018) - Guha, Ashrith; Nguyen, Duc; Cruz-Solbes, Ana S.; Amione-Guerra, Javier; Schutt, Robert C.; Bhimaraj, Arvind; Trachtenberg, Barry H.; Park, Myung H.; Graviss, Edward A.; Gaber, Osama; Suarez, Erik; Montane, Eva; et al.
Abstract : Patients bridged to transplant (BTT) with continuous-flow left ventricular assist devices (CF-LVADs) have increased in the past decade. Decision support tools for these patients are limited. We developed a risk score to estimate prognosis and guide decision-making. We included heart transplant recipients bridged with CF-LVADs from the United Network for Organ Sharing (UNOS) database and divided them into development (2, 522 patients) and validation cohorts (1, 681 patients). Univariate and multivariate Cox proportional hazards models were performed. Variables that independently predicted outcomes (age, African American race, recipient body mass index [BMI], intravenous [IV] antibiotic use, pretransplant dialysis, and total bilirubin) were assigned weight using linear transformation, and risk scores were derived. Patients were grouped by predicted posttransplant mortality: low risk (⩽ 38 points), medium risk (38–41 points), and high risk (≥ 42 points). We performed Cox proportional hazards analysis on wait-listed CF-LVAD patients who were not transplanted. Score significantly discriminated survival among the groups in the development cohort (6.7, 12.9, 20.7; p = 0.001), validation cohort (6.4, 10.1, 13.6; p < 0.001), and ambulatory cohort (6.4, 11.5, 17.2; p < 0.001). We derived a left ventricular assist device (LVAD) BTT risk score that effectively identifies CF-LVAD patients who are at higher risk for worse outcomes after heart transplant. This score may help physicians weigh the risks of transplantation in patients with CF-LVAD. Abstract : Supplemental Digital Content is available in the text.